Skala Pengukuran Karakter Adil: Salah Satu Instrumen sebagai Piranti BADRANAYA (Board-game Karakter Konselor Multibudaya) - Setyaputri, Nora Yuniar; Krisphianti, Yuanita Dwi; Nawantara, Rosalia Dewi (Universitas Nusantara PGRI Kediri, 2020)
It is very important for multicultural counselor to have fairness character. At school, there is an issue of less professionalism counselors because of less fairness character. The results of preliminary study conducted at undergraduate’s students of Guidance and Counseling Department at University of Nusantara PGRI Kediri prove that the students as candidate of counselor still discriminate the personality of counselee, less neutral when counselee tells the problem, and give labeling on counselee. Therefore, it is important to do special interventions to improve their fairness character become competent multicultural counselors. To Intervent the candidate of counselors can use certain media such as BADRANAYA (Multi-Cultural Character Board-game Counselor). The aim of this research is to develop BADRANAYA which can be accepted theoritically and practically. The research method used is research and development (Borg & Gall 1983). At present, the research process is in the third procedure namely the Development of Initial Product Draft, one of them is preparation of instruments.The validity and reliability are very important to obtain valid data regarding the level of fairness character for candidate of multicultural counselors. This article is limited to the validity and reliability of the Fairness Character Measurement Scale. Based on the results of the validity which is tested to 32 undergraduate students at University of Nusantara PGRI Kediri obtained 12 valid items with a reliability index of 0.834. The 12 items also have a very high reliability index that is represented each indicator of fairness character. While the results of the validation of the instrument, the fairness character measurement scale can be used as a measurement of the fairness character of candidate multicultural counselors in the next research procedure.